Pavlov in America: A Heterodox Approach to the Study of his Influence - Ruiz, Gabriel; Sánchez, Natividad; Gonzalo de la Casa, Luis (The Spanish Journal of Psychology, 2003)
This work presents a critical analysis of Pavlov’s influence that goes beyond the conventional view: that which reduces his influence in American psychology to the behaviorism of Watson and Hull. In order to understand the nature of the Russian physiologist’s influence in American psychology, we propose a distinction between three approaches to it: 1) the symbolic approach, on representing a model of the possibility of constructing an objective psychology; 2) the methodological approach, given the importance of the technique of conditional reflexes; and 3) the theoretical approach, which is derived from his theory of higher nervous activity. This perspective permits us to suggest that most of Pavlov’s influence on behaviorism was of a symbolic and methodological nature—though the methodological influence also reached other authors that did not belong to the behaviorist traditions, as was the case of Mateer. As far as the theoretical influence is concerned, our work proposes that it is more visible in authors such as Gantt and Liddell, or even in authors such as Boldirev, Director of the Pavlovian Laboratory at the Battle Creek Sanitarium in Michigan. The case of Gantt is especially interesting because, in addition to his important contributions, he played an essential role in the foundation of the Pavlovian Society, and the journal Conditional Reflex. What our work proposes is that to understand the nature of Pavlov’s influence in American psychology it is necessary to take into account the very characteristics of that psychology: its pragmatic interests, its methodological rigor, the dominant systems of neo-behavioral theory and the changes that occurred after the Second World War.